Lactulose with synergists supplementation improving a health of chicks and reducing the environmental burden in poultry industry - Gorlov, Ivan Fiodorovich; Slozhenkina, Marina Ivanovna; Mosolova, Daria Aleksandrovna; Khoroshevskaya, Lyudmila Viktorovna; Komarova, Zoya Borisovna; Nikulin, Vladimir Nikolaevich; Struk, Evgeniya Aleksandrovna; Khoroshevsky, Aleksey Petrovich; Anisimova, Elena Yurievna (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The study aims to understand the effect of new antibiotic-substituting supplements in feeding chickens of the Hisex Brown cross in industrial conditions. Materials and Methods: A total of 216 hatched chicks were randomly selected and distributed into Control, Test I, and Test II groups, with 3 replicates of 24 birds in three treatments. Results: At the end of the experiment, BW of T1/T2 birds was higher by 6.12% (p <0.01) and 10.29% (p <0.001) than CON. In comparison with the control hens, T1/T2 birds had a higher feed conversion rate and digestibility of nutrients. The blood indicators of T1/T2 hens exceeded those in control. Prebiotic supplementations were positively influenced in the immune indices of birds. IgA, IgG, IgM increased in groups T1/T2. Similar regularity was found in the natural resistance of chicks fed S1/S2. In the caecum, the Lactobacilli number was higher than in CON by 17.03% (p <0.01) in T1 and by 18.47% (p <0.01)—in T2; Bifidobacteria—by 17.94 (p <0.001) and 19.09% (p <0.01), respectively; at the same time, the number of E. coli decreased by 21.05% (p <0.01) and 24.21% (p <0.01). The concentration of emitted excreta noxious gases decreased: ammonia by 22.40%–24.95% (p <0.01); hydrogen sulfide by 10.67%–16.00% (p <0.01); and mercaptans by 12.90%–17.74% (p <0.05). Conclusion: These findings support the use of lactulose-based supplements as antibiotic alternatives to improve production in poultry farming and to reduce the toxic load on the environment. Adv. Vet. Anim. Res., 11(2): 429-438, June 2024 http://doi.org/10.5455/javar.2024.k792